Técnicas de diagnóstico para a Identificacao de Pára-raios Convencionais (SiC) Defeituosos em Serviço nas Redes Elétricas de Alta Tensao - Aquino, Claudio Vara (1993)
Surge arresters are applied to protect electrical apparatus against overvoltages. Many arresters have been damage before the expected operating lifetime of the main equipment they are protecting, usually 25-30 years. The paper presents laboratory and field tests that are being performed to fully investigate the performance of conventional silicon carbide gapped arresters and the main causes of their failures. Diagnosis techniques for monitoring the conditions of surge arresters in service, to detect suspected units, are compared. Special attention is given to their field execution easiness and reliability.